Lendatus, a new genus of Xanthopygina (Coleoptera: Staphylinidae: Staphylininae) with description of three new species - Stylianos Chatzimanolis (PeerJ, 2019)
A new genus of Xanthopygina rove beetles is described here as Lendatus gen. nov. The new genus includes three new species: L. bolivianus sp. nov., described from Bolivia, L. philothalpiformis sp. nov. described from Costa Rica and Panama, and L. platys sp. nov. described from Bolivia, Colombia, Ecuador and Peru. Lendatus belongs to the Isanopus group of genera of Xanthopygina and can distinguished from all the genera based on the unique punctation on the pronotum and the long apical setae of the paramere. A key to the three species of Lendatus along with photographs and illustrations is provided for the identification of species.